Discordant patterns between nitrogen-cycling functional traits and taxa in distant coastal sediments reveal important community assembly mechanisms - Song, Wen; Li, Hongjun; Zhou, Yuqi; Liu, Xia; Li, Yueyue; Wang, Mengqi; Li, Dan-dan; Tu, Qichao (Frontiers in Microbiology, 2023)
A central question in microbial ecology is how immense microbes are assembled in changing natural environments while executing critical ecosystem functions. Over the past decade, effort has been made to unravel the contribution of stochasticity and determinism to the compositional of microbial communities. However, most studies focus on microbial taxa, ignoring the importance of functional traits. By employing shotgun metagenomic sequencing and state-of-the-art bioinformatics approaches, this study comprehensively investigated the microbially mediated nitrogen (N) cycling processes in two geographically distant coastal locations. Both shotgun and 16S rRNA gene amplicon sequencing demonstrated significantly differed taxonomic compositions between the two sites. The relative abundance of major microbial phyla, such as Pseudomonadota, Thaumarchaeota and Bacteroidota, significantly differed. In contrast, high homogeneity was observed for N-cycling functional traits. Statistical analyses suggested that N-cycling taxonomic groups were more related to geographic distance, whereas microbial functional traits were more influenced by environmental factors.Multiple community assembly models demonstrated that determinism strongly governed the microbial N-cycling functional traits, whereas their carrying taxonomic groups were highly stochastic. Such discordant patterns between N-cycling functional traits and taxa demonstrated an important mechanism in microbial ecology in which essential ecosystem functions are stably maintained despite geographic distance and stochastic community assembly.